2012
DOI: 10.1111/j.1365-2672.2012.05408.x
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium toxicity is alleviated by AtLCD and AtDCD inEscherichia coli

Abstract: Aims: Arabidopsis thaliana L-and D-cysteine desulfhydrases (AtLCD and AtDCD) are two important H 2 S-generating enzymes. This study determined the effects of H 2 S derived from AtLCD and AtDCD on cadmium (Cd) toxicity in Escherichia coli. Methods and Results: AtLCD and AtDCD were cloned into pET28a vectors and transformed into wild-type E. coli strain BL21(DE3), named BL21(LCD) and BL21(DCD). In the induced BL21(LCD) and BL21(DCD) compared with wild type, significantly higher H 2 S generation rates were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…H 2 S promotes root organogenesis (Zhang et al ), seed germination (Zhang et al , ), lateral root formation (Fang et al ), and enhances photosynthesis (Chen et al ). Moreover, H 2 S confers protective roles in responses to heat, drought, salt, osmotic, and freezing stresses (Wang et al ; Zhang et al , ; Jin et al , ; Shen et al , ; Xie et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…H 2 S promotes root organogenesis (Zhang et al ), seed germination (Zhang et al , ), lateral root formation (Fang et al ), and enhances photosynthesis (Chen et al ). Moreover, H 2 S confers protective roles in responses to heat, drought, salt, osmotic, and freezing stresses (Wang et al ; Zhang et al , ; Jin et al , ; Shen et al , ; Xie et al ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, several proteins have been reported to be directly responsible for H 2 S generation in Arabidopsis , including L ‐cysteine desulfhydrase (LCD), D ‐cysteine desulfhydrase 1 (DCD1), D ‐cysteine desulfhydrase 2 (DCD2), and DES1 (Bloem et al ; Riemenschneider et al ; Papenbrock et al ; Álvarez et al , , ; Shen et al ). The knockout mutant of AtLCD ( lcd ) with decreased endogenous H 2 S level has been used to investigate the role of H 2 S in plant response to drought stress (Jin et al ), and expression of AtLCD and AtDCD1 in Escherichia coli showed increased cadmium resistance (Shen et al ). Álvarez et al (, ) found that cysteine‐generated sulfide in the cytosol affected autophagy and transcriptional profile of Arabidopsis , and knockout mutant of the DES1 shows high resistance to biotrophic and necrotrophic pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…In plants such studies are still at their beginning stages though they are attracting ever-growing attention. Currently H 2 S has been reported to participate in various physiological processes to improve drought resistance [5], [6]; increase longevity of cut flowers [7]; alleviate boron toxicity in cucumber seedlings [8]; alleviate cadmium induced oxidative damage in alfalfa seedling roots [9] and in Escherichia coli [10]; induce heat tolerance in tobacco suspension cultured cells [11]; enhance salt tolerance in alfalfa seed germination [12], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The intracellular generation of superoxide radical by cadmium (Thomas & Benov 2018), nickel and cobalt exerted toxic effects toward E. coli in which the participation of sod genes was regulated for the protection against metal stress (Geslin et al 2001). Increased production of the SOD enzyme was found in the E. coli strain BL21 and P4 in the presence of cadmium (Khan et al 2017;Shen et al 2012). v) In parallel, proteins involved in energy metabolism, e.g.…”
Section: Interconnection Between Proteins Implicated In Cadmium Stressmentioning
confidence: 99%